Know it & grow it!: empowering and educating youth in Wilson, Kansas through gardening - Ford, Sophia (My University, 2015)
In April 2013, Wilson, KS PRIDE received a grant from Kansas Community Gardens and K-State Research and Extension to fund the Wilson community garden. The garden consists of 9 plots in an area 45' x 90'. Two of the plots are devoted to youth education. My project goal was to educate youth of Wilson, Kansas about nutrition, basic biology and environmental quality through gardening. I grew up in Wilson, a rural agricultural community in central Kansas with a population of around 800, and saw this as an opportunity to give back to my community from what I learned from college at Kansas State University. While in Wilson, I assisted in the implementation of the garden, executed educational lessons for the youth of Wilson and worked with community members and Wilson schools to sustain the garden for future generations to enjoy.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Ford, S. (2013). Know it & grow it!: empowering and educating youth in Wilson, Kansas through gardening. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Wilson PRIDE, Inc.; Agriculture--Study and teaching--Kansas--Wilson; Community gardens--Kansas--Wilson; Gardening for children--Kansas--Wilson; Gardening for teenagers--Kansas--Wilson; Reports; Reports